Impact of COVID-2019 on Indian Meat Industry: National Scenario and Way Forward - Patil, Girish; Muthukumar, M.; Mendiratta, S.K.; Mandal, P.K. (Journal of Meat Science, 2016)
COVID-2019 pandemic has affected meat industry across the world and India is no exception. Meat industry plays important role in nutritional  security, employment generation and livelihood support and hence it needs to be supported at both technical and policy level. To discuss this  important issue a Cloud meeting was organized by Indian Meat Science Association on 26th April 2020 on Zoom platform. The meeting  was an attempt to put experts and stakeholders on common platform to discuss impact of the pandemic on different component of meat  industry. This document gives the crisp information of the presentations made and the issues discussed to get a national picture of the latest  developments consequent to Corona pandemic.
Keywords: Covid 19; SARS; Buffalo Meat; Poultry Sector; Meat Export